KAJIAN PSIKOLOGI SASTRA HUMANISTIK TOKOH DALAM NOVEL CERMIN TAK PERNAH BERDUSTA KARYA MIRA WIDJAJA - Tansia, Tan Ayu Felia; I Ketut Sudewa; Banda, Maria Matildis (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
The novel discussed in this study is entitled Mirror Never Lies by Mira Widjaja. In this novel, the life of a woman named Kavela is narrated who experiences bullying and physical verbal abuse because she has a bad appearance. This study aims to describe the structure and describe the needs of the hierarchy of characters in the novel. The method used for data collection is technique, observe, and record, the method of data analysis uses descriptive analytic methods, and the method of presenting the results of the analysis is descriptive. The result of the analysis are presented in a thesis format using the scientific variety of Indonesian. The theory used is structural theory to analyze plot, characters, setting, theme, style and tone. The humanistic psychological theory initiated by Abraham Maslow is used to analyse the hierarchical needs of the characters in the novel which are divided into five, including (1) psychological needs; (2) safety needs; (3) love and belonging; (4) esteem needs; and (5) self actualization needs.